2014
DOI: 10.1136/tobaccocontrol-2013-051362
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical impacts of a range of major tobacco retail outlet reduction interventions: modelling results in a country with a smoke-free nation goal

Abstract: Objective To inform endgame strategies in tobacco control, this study aimed to estimate the impact of interventions that markedly reduced availability of tobacco retail outlets. The setting was New Zealand, a developed nation where the government has a smokefree nation goal in 2025. Methods Various legally mandated reductions in outlets that were phased in over 10 years were modelled. Geographic analyses using the road network were used to estimate the distance and time travelled from centres of small areas to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…Second, it suggests that large changes in availability could have dramatic impacts in use. Pearson et al 33 examined the effect of reducing tobacco availability in New Zealand using a model that predicted behaviour change based on a continuous function of travel times translated into increased costs and found limited effects of a 95% reduction in the number of outlets. However, a threshold model would suggest that the impact of a major reduction would vary depending on the details of how that reduction was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it suggests that large changes in availability could have dramatic impacts in use. Pearson et al 33 examined the effect of reducing tobacco availability in New Zealand using a model that predicted behaviour change based on a continuous function of travel times translated into increased costs and found limited effects of a 95% reduction in the number of outlets. However, a threshold model would suggest that the impact of a major reduction would vary depending on the details of how that reduction was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, jurisdictions have implemented zoning restrictions limiting the distance that tobacco retailers can be located to a school 17. In NZ, there is strong support for a reduction of tobacco outlets around schools,18 and recent modelling has demonstrated that eliminating tobacco outlets within 2 km of a school would lead to a reduced smoking prevalence 19. Policymakers should consider restricting the density of tobacco retail outlets around schools to reduce smoking initiation and opportunities to purchase tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to calls by multiple commentators to review tobacco retailing and its regulation, with a focus on decreasing the number of retailers 3 7–11. A reduction in retailer numbers could be achieved through a number of mechanisms: a sharp increase in the price of an annual tobacco retailer license,12 a progressive reduction (or ‘sinking lid’) in the number of retailer licenses,13 restrictions on the number and location of retailers,7 incentives for retailers to stop selling tobacco8 and banning tobacco sales at pharmacies where such sales are permitted 3…”
Section: Introductionmentioning
confidence: 99%